A roadmap for the Human Developmental Cell Atlas - Haniffa, Muzlifah; Taylor, Deanne; Linnarsson, Sten; Aronow, Bruce J.; Bader, Gary D.; Barker, Roger A.; Camara, Pablo G.; Camp, J. Gray; Chédotal, Alain; Copp, Andrew; Etchevers, Heather C.; Giacobini, Paolo; et al. (Nature (London), 2021)
The Human Developmental Cell Atlas (HDCA) initiative, which is part of the Human Cell Atlas, aims to create a comprehensive reference map of cells during development. This will be critical to understanding normal organogenesis, the effect of mutations, environmental factors and infectious agents on human development, congenital and childhood disorders, and the cellular basis of ageing, cancer and regenerative medicine. Here we outline the HDCA initiative and the challenges of mapping and modelling human development using state-of-the-art technologies to create a reference atlas across gestation. Similar to the Human Genome Project, the HDCA will integrate the output from a growing community of scientists who are mapping human development into a unified atlas. We describe the early milestones that have been achieved and the use of human stem-cell-derived cultures, organoids and animal models to inform the HDCA, especially for prenatal tissues that are hard to acquire. Finally, we provide a roadmap towards a complete atlas of human development. This Perspective outlines the Human Developmental Cell Atlas initiative, which uses state-of-the-art technologies to map and model human development across gestation, and discusses the early milestones that have been achieved.